2001
DOI: 10.1143/jjap.40.1140
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of Double-Pulse Discharge in Excimer Laser with Gas Flow

Abstract: In a recent theoretical investigation of positron diffusion in gases, Shizgal and Ness suggest that the results for helium obtained by their method of solution of the diffusion equation differ in a few significant details from the earlier results of Campeanu and Humberston. It is explained here that the apparent discrepancies arise from misunderstandings in the interpretation of the earlier work and that, consequently, the results of the two methods are in good agreement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2007
2007
2007
2007

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…The supersonic nozzle is designed as a shock-free contour, which generates a uniform flow with a Mach number (M) of 2 and a velocity of 860 m/s at the nozzle exit (200 mm W Â 22:7 mm H ). A mixture of He and Ar is used in our experiments because of the following reasons: 7) (a) A large amount of gas is necessary in a discharge experiment using a flow; hence, it is not economical to use an expensive laser gas or a halogen gas that is difficult to handle. (b) Helium is commonly used as a buffer gas in excimer lasers.…”
Section: Flow Generatormentioning
confidence: 99%
See 1 more Smart Citation
“…The supersonic nozzle is designed as a shock-free contour, which generates a uniform flow with a Mach number (M) of 2 and a velocity of 860 m/s at the nozzle exit (200 mm W Â 22:7 mm H ). A mixture of He and Ar is used in our experiments because of the following reasons: 7) (a) A large amount of gas is necessary in a discharge experiment using a flow; hence, it is not economical to use an expensive laser gas or a halogen gas that is difficult to handle. (b) Helium is commonly used as a buffer gas in excimer lasers.…”
Section: Flow Generatormentioning
confidence: 99%
“…In our previous study, 7) a double-pulse discharge method was performed in a subsonic flow with a velocity of 200 m/s and it was shown that the second discharge in the sequence of pulse discharges is a glow at a pulse repetition frequency f below 3 kHz. A glow could also be produced in the second discharge along the center line of electrodes at f $ 5 kHz.…”
Section: Introductionmentioning
confidence: 99%
“…The reasons why such mixture is used have been given in detail elsewhere. 8,10) The test section consists of a nozzle, electrodes with a length of 120 mm, a width of 40 mm, and a top radius of 100 mm, UV pins, dielectric insulators, and a diffuser, as shown in the upper part of Fig. 1(b).…”
Section: Methodsmentioning
confidence: 99%
“…Many attempts have been made to increase the repetition rate of an excimer laser [1][2][3][4][5][6][7][8][9] to satisfy the requirements of the many potential applications. Chang, 4) Hermsen, 5) and Ishii et al 6) developed new electrode shapes to obtain a uniform electric field distribution in a discharge cavity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation